Pengabdian Mahasiswa Di Masyarakat Terpencil (Studi PAR di Cigarukgak, Desa Sukatani, Kecamatan Sukatani, Kabupaten Purwakarta) - Saepudin, Ahmad; Setiawati, Ayu Fajar; Koyim, Nanang (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
As stated in the Tri Dharma Perguruan Tinggi PTKIN or PTAKIS, students are not only required to get education and research through on-campus learning, but also students are required to devote themselves to the community with the real world of life. This service aims to provide problem solving solutions and empower the potential that exists in the environment. The method of community service activities is to go directly to the field, with initial observations, interviews and documentation as evidence for the report. The method in writing reports is descriptive analysis of field data by developing steps from programmers and analysis. Program activities that exist in the community or not, students directly form and provide counselling and soft skills to the community. Students must also be familiar with Islamic Economics which was developed through the Purwakarta Islamic Economic Community (MES), or be able to respond to the MEA (Asean Economic Community) era and global life. In addition, it is also to function religious social institutions and human empowerment through SMEs, agriculture and plantations.